Endothelial adhesion molecules and multiple organ failure in patients with severe sepsis. (December 2016) - Amalakuhan, Bravein; Habib, Sheila A.; Mangat, Mandeep; Reyes, Luis F.; Rodriguez, Alejandro H.; Hinojosa, Cecilia A.; Soni, Nilam J.; Gilley, Ryan P.; Bustamante, Carlos A.; Anzueto, Antonio; Levine, Stephanie M.; Peters, Jay I.; et al.
Highlights: VEGF, ICAM-1, and VCAM-1 are a group of key vascular endothelial proteins. Elevated ICAM-1 levels predict multi-organ failure (MOF) during sepsis. Elevated VCAM-1 levels predict MOF and in-hospital mortality during sepsis. Abstract: Objective: To determine if serum levels of endothelial adhesion molecules were associated with the development of multiple organ failure (MOF) and in-hospital mortality in adult patients with severe sepsis. Design: This study was a secondary data analysis of a prospective cohort study. Setting: Patients were admitted to two tertiary intensive care units in San Antonio, TX, between 2007 and 2012. Patients: Patients with severe sepsis at the time of intensive care unit (ICU) admission were enrolled. Inclusion criteria were consistent with previously published criteria for severe sepsis or septic shock in adults. Exclusion criteria included immunosuppressive medications or conditions. Interventions: None. Measurements: Baseline serum levels of the following endothelial cell adhesion molecules were measured within the first 72 h of ICU admission: Intracellular Adhesion Molecule 1 (ICAM-1), Vascular Cell Adhesion Molecule-1 (VCAM-1), and Vascular Endothelial Growth Factor (VEGF). The primary and secondary outcomes were development of MOF (⩾2 organ dysfunction) and in-hospital mortality, respectively. Main results: Forty-eight patients were enrolled in this study, of which 29 (60%) developed MOF. Patients that developed MOF had higher levels of VCAM-1 (p = 0.01) and ICAM-1 (p = 0.01), but not VEGF (p = 0.70) compared with patients without MOF (single organ failure only). The area under the curve (AUC) to predict MOF according to VCAM-1, ICAM-1 and VEGF was 0.71, 0.73, and 0.54, respectively. Only increased VCAM-1 levels were associated with in-hospital mortality (p = 0.03). These associations were maintained even after adjusting for APACHE and SOFA scores using logistic regression. Conclusions: High levels of serum ICAM-1 was associated with the development of MOF. High levels of VCAM-1 was associated with both MOF and in-hospital mortality.